TIPE DAN FUNGSI PENGUTIPAN DI BAGIAN PENDAHULUAN ARTIKEL JURNAL BERBAHASA INDONESIA - Safnil Arsyad; NFN Arono; Juni Syaputra; NFN Susilawati; Refni Susanti; NFN Musarofah (Linguistik Indonesia, 2016)
The author’s style in citing prior knowledge is an essential element determining the quality of an academic writing, such as thesis, dissertation, essay and journal article. The purpose of this study is to investigate the types and functions of citation in Indonesian article introductions written by Indonesian writers in multiple disciplines published in Indonesian research journals mainly by university based publishers. As many as 160 article introductions in education, social sciences and humanities, science and technology and health and medical sciences (i.e., forty articles in each discipline) were analyzed on their citation types and functions in the introduction section of the articles using genre-based analisys method. The results show that in terms of the use of citation types, the Indonesian article introductions are similar to those in English articles but not in terms of the use of citation function. Unlike in English journal articles, the main functions of citation in Indonesian article introductions are to support the importance of the research topic, to justify the research problem, and to present positive justification towards the information in the cited references.